Mathematical model of evaluating dissipated pollution and its numerical realization - Kleiza, Vytautas; Sakalauskienė, Gaudenta (Lietuvos matematikos rinkinys, 2002)
The paper considers pollution spreading models, based on turbulent diffusion equation, as well as their numerical realization using particular data of rivers in Lithuania.